EFFECT OF PEPPERMINT (MENTHA PIPERITA) POWDER ON PERFORMANCE, GUT MORPHOLOGY AND IMMUNE ORGANS RESPONSE OF COCCIDIOSIS INFECTED BROILERS - Hussein, S. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This experiment was performed to find out the effect of peppermint on the performance, gut morphology and immune organs of coccidiosis challenged broilers. A feeding trail was conducted on 320-day-old Ross 308 chicks allocated to 32 floor pens in a 2x4 factorial arrangement. The studied factors were: challenge (Negative or Positive) and feed additive (Control, Peppermint and). On day 8 of age, birds in challenged groups were orally inoculated with Eimeria tenella. On day 35 Eimeria decreased weight (P <.0001) gain and deteriorated feed conversion ratio (P < 0.05). On 24 and 35 days of age, broilers given salinomycin and peppermint had improved weight gain and feed conversion ratio compared to controls (P < 0.05). Significant challenge × additive interactions were observed for weight gain, feed intake, feed conversion ratio villus height, crypt depth and apparent villus surface area on d 24 and d 35. Challenged broilers in salinomycin and peppermint groups had significantly increased villus height and villus height/crypt depth and decreased crypt depth compared to positive control. Challenged birds exhibited significantly longer, wider and larger area of bursa of Fabricius lymphoid follicles compared to non-challenged birds. These results illustrated that, peppermint has high protective efficacy against declining in the performance and gut health of coccidiosis infected broilers.